Kinetics of Amyloid β monomer to oligomer exchange by NMR Relaxation - Fawzi, Nicolas L. (2010)
Recent studies implicating non-fibrillar oligomers of the amyloid β (Aβ) peptide as the primary toxic species in Alzheimer’s disease have made Aβ oligomers the subject of intense study. Detailed structural and kinetic characterization of these states, however, has been difficult. Here we use NMR relaxation measurements to address the kinetics of exchange between monomeric and large, polymorphic oligomeric species of Aβ (1–40). (15)N-R(2) and (1)H(N)-R(2) data at multiple magnetic fields were recorded for several peptide concentrations subsequent to the establishment of a stable pseudo-equilibrium between monomeric and NMR invisible soluble oligomeric species. The increase in (15)N- and (1)H(N)-R(2) rates as a function of protein concentration is independent of nucleus and magnetic field and shows only a small degree of variation along the peptide chain. This phenomenon is due to a lifetime broadening effect arising from the unidirectional conversion of monomer to the NMR invisible oligomeric species (‘dark’ state). At a total Aβ(1–40) concentration of 300 µM, the apparent first order rate constant for this process is ~3 s(−1). Fitting the McConnell equations for two dipolar-coupled spins in two-site exchange to transfer-of-saturation profiles at two radiofrequency field strengths gives an estimate for k(off) of 73 s(−1) and transiently-bound-monomer (1)H(N)-R(2) rates of up to 42,000 s(−1) in the tightly bound central hydrophobic region and ~300 s(−1) in the disordered regions such as the first nine residues. The fraction of peptide within the ‘dark’ oligomeric state undergoing exchange with free monomer is calculated to be ~3%. The relatively rapid exchange between the monomer and the polymorphic oligomeric form suggests that therapeutic efforts aimed at altering the equilibrium distribution between these species may be more successful than for the extremely stable fibril form.